Implementation of Supreme Court Regulation No 7 of 2022 concerning electronic case administration and court proceedings at The Denpasar District Court - Ragawati, Ni Ketut; Sihotang, Erikson; Saputra, Komang Edy Dharma (International Journal Labs, 2024)
The implementation of electronic trials (e-Litigation) at the Denpasar District Court is a significant step forward in the modernization of the judicial system. This study aims to find out the implementation of the electronic trial and the obstacles encountered during its implementation. The research contributes by providing insights into the practical challenges of adopting electronic trials in a specific judicial context, potentially offering recommendations for overcoming these obstacles. The findings could be valuable for policymakers, legal practitioners, and other courts looking to optimize their own implementation of e-Court.